Magnetic Resonance Images Implicate That Glymphatic Alterations Mediate Cognitive Dysfunction in Alzheimer Disease. Issue 1 (26th October 2022) - Hsu, Jung‐Lung; Wei, Yi‐Chia; Toh, Cheng Hong; Hsiao, Ing‐Tsung; Lin, Kun‐Ju; Yen, Tzu‐Chen; Liao, Ming‐Feng; Ro, Long‐Sun
Abstract : Objective: The glymphatic system cleans amyloid and tau proteins from the brain in animal studies of Alzheimer disease (AD). However, there is no direct evidence showing this in humans. Methods: Participants (n = 50, 62.6 ± 5.4 years old, 36 women) with AD and normal controls underwent amyloid positron emission tomography (PET), tau PET, structural T1‐weighted magnetic resonance imaging, and neuropsychological evaluation. Whole‐brain glymphatic activity was measured by diffusion tensor image analysis along the perivascular space (DTI‐ALPS). Results: ALPS‐indexes showed negative correlations with deposition of amyloid and tau on PET images and positive correlations with cognitive scores even after adjusting for age, sex, years of education, and APOE4 genotype covariates in multiple AD‐related brain regions (all p  < 0.05). Mediation analysis showed that ALPS‐index acted as a significant mediator between regional standardized uptake value ratios of amyloid and tau images and cognitive dysfunction even after correcting for multiple covariates in AD‐related brain regions. These regions are responsible for attention, memory, and executive function, which are vulnerable to sleep deprivation. Interpretation: Glymphatic system activity may act as a significant mediator in AD‐related cognitive dysfunction even after adjusting for multiple covariates and gray matter volumes. ALPS‐index may provide useful disease progression or treatment biomarkers for patients with AD as an indicator of modulation of glymphatic activity. ANN NEUROL 2023;93:164–174